Survivors' perspectives on risks and benefits of Hodgkin lymphoma treatment: results of a survey by the German Hodgkin Study Group. Issue 6 (12th May 2019) - Kreissl, Stefanie; Goergen, Helen; Müller, Horst; Meissner, Julia; Mehnert, Anja; Bürkle, Carolin; Fuchs, Michael; Engert, Andreas; Behringer, Karolin; Borchmann, Peter
Abstract: We performed a survey in Hodgkin lymphoma survivors to learn more about their perspectives on treatment risks and benefits. We sent questions to 1149 survivors from the GHSG's HD13-15 trials with ( N = 249) or without ( N =900) documented progression or relapse. The participation rate was 52% ( N =581). After median follow-up of 106 months, 40% of relapse-free and over 60% of relapsed survivors were still worried about late effects and the possibility of relapse. Chemotherapy, largely independent of its intensity, had been a strain on 74% of relapse-free and 90% of relapsed survivors. Most physical, psychological, and socio-economic sequelae were more frequent among relapsed survivors ( p < .05) and described as very burdensome. 74% of relapse-free and 61% of relapsed survivors considered primary cure from Hodgkin lymphoma as the most important aspect in the choice of treatment. Accordingly, primary optimal lymphoma control is of utmost importance from the patients' perspective.